2010
DOI: 10.1007/s10620-010-1190-9
|View full text |Cite
|
Sign up to set email alerts
|

Urinary and Fecal Incontinence After Bariatric Surgery

Abstract: Both fecal and urinary incontinence were common after bariatric surgery. Risk factors for fecal incontinence in women after bariatric surgery include diarrhea and worsening of diarrhea; we suggest that such surgery may uncover prior weaknesses in the continence mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 24 publications
1
36
1
Order By: Relevance
“…My results are similar to those of most studies which show a positive association between IBS and general obesity [15,16,17]; and between IBS and central obesity [14]. Some studies show that central obesity using WC is more associated with IBS than general obesity [18,19].…”
Section: Association Between Central Obesity and Ibssupporting
confidence: 88%
“…My results are similar to those of most studies which show a positive association between IBS and general obesity [15,16,17]; and between IBS and central obesity [14]. Some studies show that central obesity using WC is more associated with IBS than general obesity [18,19].…”
Section: Association Between Central Obesity and Ibssupporting
confidence: 88%
“…Diarrhoea can also occur following bariatric surgery with an incidence of up to 40% 95. Rarely, this can deteriorate to the point of faecal incontinence 95.…”
Section: Reviewmentioning
confidence: 99%
“…Likewise, a recent study found that women submitted to bariatric surgery followed by weight loss experienced improvements in urinary loss and in the frequency and severity of FI [19].…”
Section: Discussionmentioning
confidence: 92%
“…In a study by Roberson et al 2010, 48% of women and 42% of men after bariatric surgery reported incontinence for liquid stool, and 21% of women and 30% of men reported incontinence to solid stool. Risk factors for FI in obese after bariatric surgery include diarrhea and worsening diarrhea (disabsortive surgeries), and also, this surgery can reveal weaknesses in previous continence mechanism [22].…”
Section: Discussionmentioning
confidence: 98%